Implementation of The Olericulture Program in Realizing a Green School at SD Inpres Perumnas 1 Rappocini Makassar City - Alam, Nadia S.; Ahmad, M. Ridwan Said; Sidik, Ramdani; Reski, Sulfa (Citra Media Publishing, 2025)
This study aims to analyze the implementation of the olericulture program as a form of integrating environmental education at SD Inpres Perumnas 1 Rappocini, Makassar City. The program focuses on cultivating horticultural vegetables as a contextual learning medium to foster ecological awareness and character values among elementary school students. The research employed a descriptive qualitative approach using field observations, interviews, and photographic documentation as the main data sources. Data were analyzed through stages of reduction, presentation, and conclusion drawing, emphasizing data validity through source triangulation. The findings reveal two key results. First, the olericulture activities at this school have created a participatory, ecology-based learning space that involves students, teachers, and the principal in a collaborative learning system. Through the practice of planting, caring for, and harvesting vegetables, students gain direct experiences that highlight the interrelationship between humans and nature, as well as values of responsibility and cooperation. Second, the implementation of this program demonstrates the school’s transformation toward a green school model that emphasizes sustainable learning and character building. This program aligns with the principles of ESD, which views education as a transformative process to foster ecological awareness and action from an early age. The study confirms that the olericulture program can serve as a relevant model for environmental education in elementary schools, particularly in urban areas with limited green space. The success of this program indicates that integrating ecological practices, project-based learning, and local values can strengthen students’ environmental literacy. The research recommends greater curriculum support, teacher training, and cross-sector partnerships to expand community-based green school models in Indonesia.